Preparation and Characterization of Barium and Strontium Hexaferrite Employing Recycled Millscale - Azis, Raba'ah Syahidah (2003)
In this project work, permanent magnet barium/ strontium hexaferrite materials was prepared from millscale, using hematite derived from millscale by the Curie Temperature Separation Technique (CTST). The excellent CTST isolation and purification of wustite,FeO contained in the millscale and converted to hematite,Fe2O3, was confirmed by X-Ray Diffraction (XRD) pattern analysis and element analysis by Electron Dispersive X-Ray (EDAX). The sample was prepared by recycling the waste product from Malaysian steel-making factories. Using a Curie temperature separation technique, the wustite,FeO contained in the millscale was separated by this new technique using deionized water at 90oC/100oC in the presence of 1T external magnetic field. The wustite iv was then oxidized in air at 400oC/500oC/600oC for 10 hours. An XRD phase analysis showed that a very high percentage of Fe2O3 was present in the final powder preparation. A conventional ceramic powder processing method was then carried out to prepare hexagonal BaFe12O19 and SrFe12O19 pallet shaped samples. Analysis of samples was done on density, resistivity, X-Ray Diffraction (XRD), Particle Size Analysis (PSD), Electron Dispersive X-Ray (EDAX), Scanning Electron Micrsocopy (SEM), grain size, saturation magnetization, coercive force and remanence. The effect of prolonged milling time shows a positive tendency for the formation of needle shape microstructure (0.3μm-1μm) of barium hexaferrite. The magnetic properties were measured using an Approximation Method (APM) theory. The 3.33 kG high remanence , 0.74 kG saturation magnetisation and 2.857 kOe coercive force of the sample derived from millscale shows that recycling a waste steel-making product has a high potential to produce a low cost ferrite in the future.